The association of host and genetic melanoma risk factors with Breslow thickness in the Western Australian Melanoma Health Study - Cadby, G.; Ward, S.; Cole, J.; Moses, Eric; Millward, M.; Palmer, L. (2014)
Background: Breslow thickness is the most important predictor of survival in localized malignant melanoma. A number of melanoma risk factors have been shown to be associated with Breslow thickness; however, the role of genetic loci has been little investigated to date. Objectives: To investigate the association of known melanoma susceptibility genetic loci with Breslow thickness. Methods: Participants were 800 individuals from the Western Australian Melanoma Health Study who completed a questionnaire and provided a DNA sample. Genetic association analyses between single-nucleotide polymorphisms (SNPs) from 15 candidate melanoma susceptibility genes and Breslow thickness were performed, controlling for relevant covariates. Results: Older age at diagnosis and absence of naevi were associated with increased Breslow thickness. Following adjustment for multiple testing, no SNPs were significantly associated with Breslow thickness. Conclusions: Associations observed between Breslow thickness and age and naevi reinforce current knowledge. Some evidence of shared genetic determinants between melanoma risk and Breslow thickness was found. Further studies are required to confirm this finding.